Preparation method of cellulose acetate / thermoplastic polyurethane / polypyrrole conductive nanofiber aerogel composite pressure sensing material

By preparing cellulose acetate/thermoplastic polyurethane/polypyrrole conductive nanofiber aerogels through electrospinning and low-temperature composite processes, the problems of low strength and poor compressibility caused by high-temperature carbonization were solved, realizing a flexible pressure sensor with high sensitivity and long life, suitable for human motion and health monitoring.

CN120988341APending Publication Date: 2025-11-21NANJING FORESTRY UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202410626852.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing flexible piezoresistive sensors based on nanofiber aerogels have low strength and poor compressibility during high-temperature carbonization, which cannot meet the requirements of high sensitivity, fast response and long service life. Moreover, the high-temperature and high-pressure preparation process is energy-intensive and costly, which is not conducive to large-scale production.

Method used

A low-temperature composite method combining electrospinning with cellulose acetate, thermoplastic polyurethane, and polypyrrole was adopted to prepare cellulose acetate/thermoplastic polyurethane/polypyrrole conductive nanofiber aerogels through electrospinning, homogenization, low-temperature polymerization, and freeze-drying, avoiding high-temperature thermal annealing.

Benefits of technology

The prepared aerogel has ultra-low bulk density, superelasticity and excellent piezoresistive properties, making it suitable for flexible pressure sensing materials, human motion and health monitoring. It is simple to operate, the raw materials are cheap and readily available, and it is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HSA0000297979780000011
    Figure HSA0000297979780000011
  • Figure HSA0000297979780000012
    Figure HSA0000297979780000012
  • Figure HSA0000297979780000013
    Figure HSA0000297979780000013
Patent Text Reader

Abstract

The invention discloses a preparation method of a cellulose acetate / thermoplastic polyurethane / polypyrrole composite conductive nanofiber aerogel composite pressure sensing material. The preparation method comprises the following steps: (1) preparing a cellulose acetate and thermoplastic polyurethane spinning solution; (2) preparing a cellulose acetate / thermoplastic polyurethane composite nanofiber membrane; (3) preparing cellulose acetate / thermoplastic polyurethane short nano dispersion liquid; (4) preparing a cellulose acetate / thermoplastic polyurethane / polypyrrole polymerization solution; and (5) preparing the cellulose acetate / thermoplastic polyurethane / polypyrrole composite conductive nanofiber aerogel. According to the preparation method, a high-temperature thermal annealing process is not needed, and the prepared nanofiber composite aerogel has high conductivity, ultralow volume density, high compression deformation performance and high pressure resistance sensing sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of flexible wearable electronic devices, and in particular to a preparation method of a cellulose acetate / thermoplastic polyurethane / polyazole conductive nanofiber aerogel composite pressure sensing material. BACKGROUND

[0002] With the rapid development of artificial intelligence and the Internet of Things, intelligent flexible wearable sensing technology has been everywhere, making our life more convenient. Flexible pressure sensing materials capable of converting external mechanical deformation and other stimulation signals into electrochemical signals are important structural elements in wearable devices, electronic skin, flexible batteries, biological monitors and other sensing devices, and are also the focus of developing new high-sensitivity sensors. Because of its ultra-low density, ultra-porous interconnected network and ultra-high porosity, aerogel-based flexible pressure sensing materials based on electrospun nanofibers are favored by researchers. 3D nanofiber aerogels not only inherit the traditional advantages of aerogels (such as low density, high specific surface area and large porosity), but also have the unique properties of 1D nanofibers (including excellent mechanical flexibility, wide range of material selection and additional functions). These comprehensive advantages make 3D nanofiber aerogels show great application potential in the field of pressure resistance sensing. Since its first practical application in 2014, electrospun nanofibers have brought great hope to the application of aerogel materials due to their gel-free synthesis and high controllability. From polymers, carbon, ceramics and other materials to various morphologies, structures, compositions and functions, electrospun nanofibers have brought great hope to the application of aerogel materials. Unlike traditional time-consuming aerogel preparation, electrospun nanofibers can directly form a 3D skeleton of physical entanglement and / or chemical cross-linking in the aerogel, which not only improves the porosity and specific surface area of the aerogel, but also reduces the density and brittleness of the aerogel. However, flexible pressure resistance sensors based on nanofiber aerogels are usually prepared by high-temperature carbonization to build a three-dimensional conductive network. The high-temperature pyrolysis process inevitably leads to low strength and poor compressibility of the nanofiber aerogel, which cannot meet the urgent requirements of flexible sensors for high sensitivity, fast response and long service life. In addition, the high-temperature and high-pressure preparation process also brings a lot of energy consumption and higher preparation cost.

[0003] The introduction of various conductive fillers (carbon nanotubes, graphene, metal nanowires / nanosheets, conductive polymers, etc.) combined with electrospun fibers is an effective way to solve the above problems, which not only can significantly improve the dispersibility and compressibility of the conductive fillers, but also endows the aerogel with excellent piezoresistive performance. For example, researchers used liquid nitrogen assisted unidirectional freezing method to prepare super-elastic and super-light carbon nanofiber / MXene hybrid aerogel with anisotropic microchannels for flexible piezoresistive sensing and supercapacitor electrodes. The carbon nanofibers with high aspect ratio are intertwined to form a three-dimensional scaffold, while the MXene nanosheets enhance the structural stability of the carbon nanofiber framework and endow the aerogel with excellent electrical conductivity. However, the preparation process of these nanomaterials is complex and costly, which is not conducive to large-scale production. The development of conductive nanofiber aerogel by using conductive polymers as sensing active materials and nanofibers is expected to overcome the current problems.

[0004] Most conductive polymers not only have good photoelectric properties, but also can introduce more functions after being doped with other materials. Among them, polypyrrole is widely used in the fields of microwave absorption, photoelectricity and sensing due to its simple preparation process, high electrical conductivity and good biocompatibility. However, the loose physical structure of polypyrrole prepared by chemical method makes the sensing performance and mechanical properties of polypyridyl-based flexible piezoresistive sensors far from satisfactory. SUMMARY

[0005] The technical problem to be solved by the present application is to provide a method for preparing cellulose acetate / thermoplastic polyurethane / polypyrrole conductive nanofiber aerogel composite pressure sensing material without heat annealing and carbonization, which combines electrospinning, homogeneous dispersion, low temperature polymerization and freeze drying. The obtained cellulose acetate / polypyrrole composite conductive nanofiber aerogel has ultra-low bulk density, super-elasticity and excellent piezoresistive performance.

[0006] In order to achieve the above-mentioned application purposes, the technical scheme adopted by the present application is as follows: a preparation method of cellulose acetate / thermoplastic polyurethane / polypyrrole conductive nanofiber aerogel composite pressure sensing material, comprising the following steps:

[0007] (1) Weigh cellulose acetate (CA) powder and dissolve it in acetone and N,N-dimethylacetamide, stir and prepare cellulose acetate spinning solution, and store for later use;

[0008] (2) Weigh thermoplastic polyurethane (TPU) particles and dissolve them in acetone and N,N-dimethylacetamide, stir and prepare thermoplastic polyurethane spinning solution, and store for later use;

[0009] (3) mixing and stirring the solution in step (1) and step (2) uniformly, preparing CA-TPU nanofiber membrane by electrospinning technology, and then placing in an oven for drying;

[0010] (4) adding the dried CA-TPU nanofiber membrane in step (3) into deionized water, and then adding polyvinylpyrrolidone (PVP) for homogeneous dispersion, to prepare CA-TPU short nanodispersion;

[0011] (5) further dispersing the CA-TPU short nanodispersion prepared in step (4) by using an ultrasonic disrupter, and then adding ferric chloride hexahydrate and pyrrole (Py) monomer thereto, and performing polymerization in a low-temperature reaction bath;

[0012] (6) placing the polymerized solution in step (5) into a refrigerator for freezing, and then freeze-drying to obtain CA / TPU / PPy composite conductive nanofiber aerogel.

[0013] Further, the concentration of the CA solution in step (1) is 14wt%-20wt%, preferably 18wt%.

[0014] Further, the thermoplastic polyurethane (TPU) in step (2) is a thermoplastic polyurethane elastomer produced by BASF SE, Germany, with a model number of TRU-685A, and the solution concentration is 15wt%-20wt%, preferably 15wt%.

[0015] Further, in steps (1) and (2), the mass ratio of acetone and N,N-dimethylacetamide is 2:1.

[0016] Further, in step (3), the mass ratio of CA solution and TPU solution is 1:(0.5-2), preferably 1:0.5.

[0017] Further, in step (3), the electrospinning conditions are as follows: voltage 14-20kV, needle flow rate 0.5-1mL / h, distance between needle and roller receiver 10-15cm, and roller receiver rotation speed 200-500rpm.

[0018] Further, the concentration of the CA-TPU short nanodispersion in step (4) is 0.2wt%-1wt%, preferably 0.5wt%.

[0019] Further, the mass of the added PVP in step (4) is 10-50mg.

[0020] Further, the mass ratio of the ferric chloride hexahydrate and the pyrrole monomer added in step (5) is (1-5):1; the low-temperature reaction bath temperature is -1-1 DEG C, and the polymerization time is 10-14 hours.

[0021] Further, the freezing temperature in step (6) is -22- -18 DEG C, and the freezing time is 12-24 hours; the freeze drying is carried out at -80- -45 DEG C and 2-100 Pa pressure, and the freeze drying time is 24-48 hours.

[0022] The application has the beneficial technical effects that:

[0023] (1) The CA-TPU composite nanofiber is used as a three-dimensional support skeleton, and the polypyrrole high polymer is used as a conductive material, without high-temperature heat annealing, and the CA / TPU / PPy composite conductive nanofiber aerogel is prepared by combining the low-temperature freezing polymerization and freeze drying process, and the aerogel has an ultralow bulk density (17.3 mg / cm 3 ), high compression deformation performance and high fatigue resistance, and can be applied to human motion and health monitoring as a flexible piezoresistive sensing material.

[0024] (2) The introduction of the polyvinylpyrrolidone greatly promotes the dispersion of the CA-TPU short nanofiber, effectively avoids the aggregation between the short fibers and is beneficial to the subsequent polymerization of the pyrrole monomer, so as to ensure the mechanical performance of the three-dimensional framework of the aerogel.

[0025] (3) In the low-temperature reaction bath, the pyrrole monomer particles are adsorbed on the CA-TPU composite nanofiber to form a coaxial structure through strong hydrogen bonds, which forms a stable conductive shell and promotes the mutual crosslinking of the short nanofiber.

[0026] (4) The operation steps of the application are simple, the raw materials are cheap and easy to obtain, the experimental equipment requirement is low, and the application can be mass produced. BRIEF DESCRIPTION OF DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the application, the drawings needed in the embodiment description will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.

[0028] Among them:

[0029] Figure 1 The technical scheme of the application is shown in the figure.

[0030] Figure 2The mechanical property comparison chart of CA / TPU composite nanofiber aerogel prepared by the present application embodiment 1 (containing PVP) and comparative example 1 (not containing PVP), wherein the upper right corner is the morphology chart of the prepared aerogel.

[0031] Figure 3 The SEM chart (scale as shown in the figure) of CA / TPU / PPy composite conductive nanofiber aerogel prepared by the present application embodiment 2.

[0032] Figure 4 The current-time chart of human motion and physiological signal tested by the CA / TPU / PPy composite conductive nanofiber aerogel prepared by the present application embodiment 2 after being assembled into a flexible piezoresistive sensor; wherein figure A is the finger pressing motion tested by the assembled sensor; figure B is the palm opening and closing motion tested by the assembled sensor fixed on the wrist (on the same side as the palm); figure C is the wrist joint motion tested by the assembled sensor fixed on the wrist (on the same side as the back of the hand); figure D is the swallowing motion tested by the assembled sensor fixed on the Adam's apple, and figures E and F are respectively the pulse signal tested by the assembled sensor fixed on the wrist and the signal amplification chart thereof. DETAILED DESCRIPTION

[0033] In order to better understand the above-mentioned purposes, features and advantages of the present application, the specific embodiments of the present application will be described in detail below in combination with the drawings and specific embodiments.

[0034] The structures, proportions, sizes, etc. shown in the drawings of the specification are only used to cooperate with the content disclosed in the specification, to be understood and read by those skilled in the art, and are not used to limit the conditions that the present application can be implemented, so they do not have technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size, without affecting the effect and purpose that the present application can produce, should still fall within the scope of the technical content disclosed by the present application. At the same time, the terms such as "upper", "lower", "front", "rear", "middle" and the like used in the specification are only for the convenience of clear description, and are not used to limit the scope of the present application, and the change or adjustment of the relative relationship, without substantially changing the technical content, is also considered as the implementation of the present application.

[0035] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. The "in one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an independent or alternative embodiment that excludes other embodiments.

[0036] Embodiment 1

[0037] A preparation method of cellulose acetate / thermoplastic polyurethane composite nanofiber aerogel, comprising the following steps:

[0038] (1) 2.7 g of cellulose acetate powder was dissolved in a mixed solution of 10.38 mL of acetone and 4.65 mL of N, N-dimethylacetamide, and stirred at a stirring speed of 500 r / min for dissolution, to prepare a 18 wt% cellulose acetate spinning solution for storage.

[0039] (2) 3 g of thermoplastic polyurethane particles (TPU-685A produced by BASF SE, Germany) was dissolved in a mixed solution of 14.34 mL of acetone and 6.43 mL of N, N-dimethylacetamide, and stirred at a stirring speed of 600 r / min for dissolution, to prepare a 15 wt% thermoplastic polyurethane spinning solution for storage.

[0040] (3) The cellulose acetate and thermoplastic polyurethane solutions prepared in steps (1) and (2) were mixed in a mass ratio of 1:1 and uniformly mixed at a stirring speed of 600 r / min. Subsequently, the mixed solution after stirring was spun in a high-voltage electrostatic field with a voltage of 15 kV, wherein the distance from the needle tip to the receiving roller was 15 cm, the advancing speed of the spinning solution was 0.8 mL / h, and the roller speed for collecting the fibers was 300 r / min. The temperature of the spinning closed environment was controlled at 25±2℃, and the humidity was controlled at 50±5%. After collecting the CA-TPU composite nanofiber membrane, it was placed in a drying oven at 50℃ for drying for 24 h.

[0041] (4) 0.3 g of the dried CA-TPU composite nanofiber membrane was cut into small pieces (1*1 cm), 60 mL of deionized water and 15 mg of polyvinylpyrrolidone were added, and a homogenizer was used to homogenize at 11000 rpm for 15 min to form a uniformly dispersed CA-TPU short nanodispersion.

[0042] (5) The CA-TPU short nanodispersion prepared in step (4) was further dispersed by using an ultrasonic crusher (power 260 W, time 40 min), and then the CA-TPU short nanodispersion was transferred to a silica gel mold (2*2*2 cm) and placed in a freezer freezing layer (-20~-18℃) for freezing for 24 h.

[0043] (6) The frozen dispersion was placed in a freeze dryer and freeze-dried at -80℃ and a pressure of 2 Pa for 24 h to obtain a CA / TPU composite nanofiber aerogel.

[0044] Example 2

[0045] A preparation method of a cellulose acetate / thermoplastic polyurethane / polyazole conductive nanofiber aerogel composite pressure sensing material, comprising the following steps:

[0046] (1) 3.6 g of cellulose acetate powder was weighed and dissolved in a mixed solution of 13.84 mL of acetone and 6.2 mL of N,N-dimethylacetamide, stirred and dissolved at a stirring speed of 500 r / min, and configured into 18 wt% cellulose acetate spinning solution for storage.

[0047] (2) 6 g of thermoplastic polyurethane particles (TPU-685A produced by BASF SE, Germany) was weighed and dissolved in a mixed solution of 28.69 mL of acetone and 12.86 mL of N,N-dimethylacetamide, stirred and dissolved at a stirring speed of 600 r / min, and configured into 15 wt% thermoplastic polyurethane spinning solution for storage.

[0048] (3) The cellulose acetate and thermoplastic polyurethane solutions configured in steps (1) and (2) were mixed in a mass ratio of 1:1 and uniformly mixed at a stirring speed of 600 r / min. Subsequently, the mixed solution after stirring was spun in a high-voltage electrostatic field with a voltage of 15 kV, wherein the distance from the needle tip to the receiving roller was 15 cm, the advancing speed of the spinning solution was 0.8 mL / h, and the roller speed for collecting the fibers was 300 r / min. The temperature of the spinning closed environment was controlled at 25±2℃, and the humidity was controlled at 50±5%. After collecting the CA-TPU composite nanofiber membrane, it was placed in a 50℃ drying oven for drying for 24 h.

[0049] (4) 0.4 g of the dried CA-TPU composite nanofiber membrane was weighed and cut into small pieces (1*1 cm), 80 mL of deionized water and 40 mg of polyvinylpyrrolidone were added, and a homogeneous CA-TPU short nanodispersion was formed by using a homogenizer at 11000 rpm for 15 min.

[0050] (5) The CA-TPU short nanodispersion prepared in step (4) was further dispersed by using an ultrasonic crusher (power 260 W, time 40 min), 1.6 g of ferric chloride hexahydrate was added to the uniformly dispersed solution and stirred in an ice water mixed bath for 1 h, transferred to a 100 mL three-necked flask and 0.4 g of pyrrole monomer was added dropwise, and then in-situ polymerization was carried out in a low-temperature reaction bath (-1~1℃) for 12 h.

[0051] (6) The solution after polymerization in step (5) was transferred to a silica gel mold (2*2*2 cm) and placed in a freezer (-20~-18℃) for freezing for 24 h, and then placed in a freeze dryer for freeze drying at -80℃ and a pressure of 2 Pa for 24 h to obtain CA / TPU / PPy composite conductive nanofiber aerogel.

[0052] Comparative Example:

[0053] The CA-TPU composite nanofiber membrane prepared by using only CA-TPU composite nanofiber membrane without adding polyvinylpyrrolidone is compared with the material of the present application in structure and performance, etc., including the following steps:

[0054] (1) 2.7 g of cellulose acetate powder was weighed and dissolved in a mixed solution of 10.38 mL of acetone and 4.65 mL of N, N-dimethylacetamide, stirring and dissolving at a stirring speed of 500 r / min, to prepare a 18 wt% cellulose acetate spinning solution for storage.

[0055] (2) 3 g of thermoplastic polyurethane particles (TPU-685A produced by BASF SE, Germany) was weighed and dissolved in a mixed solution of 14.34 mL of acetone and 6.43 mL of N, N-dimethylacetamide, stirring and dissolving at a stirring speed of 600 r / min, to prepare a 15 wt% thermoplastic polyurethane spinning solution for storage.

[0056] (3) The cellulose acetate and thermoplastic polyurethane solutions prepared in steps (1) and (2) were mixed in a mass ratio of 1:1 and uniformly mixed at a stirring speed of 600 r / min. Subsequently, the mixed solution after stirring was spun in a high-voltage electrostatic field with a voltage of 15 kV, wherein the distance from the needle tip to the receiving roller was 15 cm, the advancing speed of the spinning solution was 0.8 mL / h, and the roller speed for collecting the fibers was 300 r / min. The temperature of the spinning closed environment was controlled at 25±2℃, and the humidity was controlled at 50±5%. After the CA-TPU composite nanofiber membrane was collected, it was placed in a 50℃ drying oven for drying for 24 h.

[0057] (4) 0.3 g of the dried CA-TPU composite nanofiber membrane was weighed and cut into small pieces (1*1 cm), 60 mL of deionized water was added, and a homogeneous CA-TPU short nanodispersion was formed by using a homogenizer at 11000 rpm for 15 min.

[0058] (5) The CA-TPU short nanodispersion prepared in step (4) was further dispersed by using an ultrasonic crusher (power 260 W, time 40 min), and then the CA-TPU short nanodispersion was transferred to a silica gel mold (2*2*2 cm) and placed in a freezer (-20~-18℃) for freezing for 24 h.

[0059] (6) The frozen dispersion was placed in a freeze dryer and freeze-dried at -80℃ and a pressure of 2 Pa for 24 h to obtain a CA / TPU composite nanofiber aerogel.

[0060] Test Example:

[0061] Mechanical performance test: the parameters of the composite nanofiber aerogel prepared by example 1-2 and the comparative example are recorded, then a universal testing machine (UTM6502, Shenzhen Sanechips Technology Co., Ltd.) is used to compress the aerogel sample at a speed of 10 mm / min, and the stress-strain curve is tested, each sample is tested at least 3 times.

[0062] Piezoresistive sensing performance test: a piezoresistive sensing performance test is performed using an electrochemical workstation (CHI660E, Shanghai Chenhua Company). The CA / TPU / PPy composite conductive nanofiber aerogel prepared in example 2 is assembled with copper tape and the like to prepare a simple device. The device is clamped by alligator clips and connected to the electrochemical workstation. The conductivity and current response change of the material are observed and recorded.

[0063] It should be noted that the above examples are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that a number of improvements and refinements can be made without departing from the spirit and scope of the technical solutions of the present application, which should be covered in the scope of the claims of the present application.

Claims

1. A method for preparing a cellulose acetate / thermoplastic polyurethane / polypyrrole conductive nanofiber aerogel composite pressure sensing material, characterized in that, The preparation method includes the following steps: (1) Weigh out cellulose acetate (CA) powder and dissolve it in acetone and N,N-dimethylacetamide. Stir to prepare cellulose acetate spinning solution and store it for later use. (2) Weigh thermoplastic polyurethane (TPU) particles and dissolve them in acetone and N,N-dimethylacetamide. Stir to prepare a thermoplastic polyurethane spinning solution and store it for later use. (3) Mix the solutions from step (1) and step (2) and stir them evenly. Prepare CA-TPU nanofiber membranes by electrospinning and then place them in an oven to dry. (4) Add the dried CA-TPU nanofiber membrane from step (3) to deionized water, and then add polyvinylpyrrolidone (PVP) for homogeneous dispersion to obtain CA-TPU short nano dispersion. (5) The CA-TPU short nano dispersion prepared in step (4) is further dispersed using an ultrasonic disruptor, and then ferric chloride hexahydrate and pyrrole (Py) monomer are added to it and polymerized in a low-temperature reaction bath. (6) The polymerized solution from step (5) is placed in a refrigerator for freezing, and then freeze-dried to obtain CA / TPU / PPy composite conductive nanofiber aerogel.

2. The preparation method according to claim 1, characterized in that, The concentration of the CA solution mentioned in step (1) is 14 wt% to 20 wt%.

3. The preparation method according to claim 1, characterized in that, The thermoplastic polyurethane (TPU) mentioned in step (2) is a thermoplastic polyurethane elastomer produced by BASF AG, Germany, model TPU-685A, and the concentration of the prepared solution is 15wt% to 20wt%.

4. The preparation method according to claim 1, characterized in that, In steps (1) and (2), the mass ratio of the solvent acetone to N,N-dimethylacetamide is 2:

1.

5. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of the CA solution to the TPU solution is 1:(0.5-2).

6. The preparation method according to claim 1, characterized in that, In step (3), the conditions for electrospinning are: voltage 14-20kV, needle flow rate 0.5-1mL / h, distance between needle and roller receiver 10-15cm, and roller receiver rotation speed 200-500rpm.

7. The preparation method according to claim 1, characterized in that, The concentration of the CA-TPU short nano-dispersion in step (4) is 0.2wt%-1wt%.

8. The preparation method according to claim 1, characterized in that, The amount of PVP added in step (4) is 10 to 50 mg.

9. The preparation method according to claim 1, characterized in that, The mass ratio of ferric chloride hexahydrate and pyrrole monomer added in step (5) is (1-5):1; the temperature of the low-temperature reaction bath is -1 to 1°C, and the polymerization time is 10 to 14 hours.

10. The preparation method according to claim 1, characterized in that, The freezing temperature in step (6) is -22 to -18°C and the freezing time is 12 to 24 hours; the freeze drying is carried out at -80 to -45°C and 2 to 100 Pa pressure for 24 to 48 hours.

Citation Information

Cited By

  • High-conductivity aerogel powder as well as preparation method and application thereof

    CN121406017A

  • Highly conductive aerogel powder, preparation method and application thereof

    CN121406017B

  • High-strength conductive aerogel powder as well as preparation method and application thereof

    CN121427169A

  • High-strength conductive aerogel powder, preparation method and application thereof

    CN121427169B